SOCIOLOGICAL VIEWS OF EASTERN SCIENTISTS ON THE WELFARE STATE - Sodikova Shohida Markhabovna (Western European Studies, 2024)
This article interprets the sociological views of Eastern scholars on society. In this regard, a sociological definition of the concept of "welfare state" was given based on the research of the views of scholars Farobi, Motrudi, Ibn Sina, Beruni, Jami, Rumi, Navai, Davani, Babur.
Keywords: welfare state; human dignit; social protection